Green Synthesis of Fe2O3 Nanoparticles Using Eucalyptus globulus Leaf Extract on Pinus radiata Sawdust for Cationic Dye Adsorption - Pablo Salgado; Eduardo Aedo; Gladys Vidal (Nanomaterials)
The present study reports the synthesis of Fe2O3 nanoparticles on Pinus radiata sawdust (Fe2O3@PS) using a Eucalyptus globulus leaf extract. The morphology and structure of Fe2O3@PS were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and UV–Vis diffuse reflectance. The adsorption capacity of the system was evaluated by testing its ability to remove the Rhodamine B (RhB) dye. The optimization of the system was carried out using the Plackett–Burman design (PBD) and the response surface methodology (steepest ascent and the Box–Behnken design), which provided information on the main parameters affecting the adsorption process. The PBD results showed that the most important parameters for the removal of RhB using Fe2O3@PS were the removal time, the RhB concentration, and the initial pH of the system. The reusability of Fe2O3@PS under optimal conditions was tested and it was found to maintain its efficiency after five cycles of use. The efficiency and rate of RhB removal observed at pH values near 7.0 were found to be predominantly influenced by electrostatic interactions. In contrast, the analyses conducted at pH values near 8.3 exhibited reduced influence from electrostatic attractions, with π–π interactions and hydrogen bonds emerging as dominant forces. At pH values exceeding 8.3, all potential interactions between RhB and Fe2O3@PS exhibited diminished strength. This research provides valuable information on the formation of eco-friendly nanoparticles immobilized on a forest residue such as sawdust, which can effectively remove organic pollutants like RhB. This contributes to the valorization of resources and the search for solutions to water pollution.